Phase formation in a calcium phosphate coating growing on a zirconium substrate with an oxide layer; Mathematical Models and Computer Simulations; Vol. 9, iss. 5 - Nazarenko N. N. Nelli Nikolaevna (2017, 2017)
Title screen